An imaging study and spectroscopic curing analysis on polymers for synthetic whole-cell receptors for bacterial detection. (17th January 2020) - Givanoudi, Stella; Gennaro, Alessia; Yongabi, Derick; Cornelis, Peter; Wackers, Gideon; Lavatelli, Alberto; Robbens, Johan; Heyndrickx, Marc; Wübbenhorst, Michael; Wagner, Patrick
Abstract: Surface imprinted polymers (SIPs) are versatile receptors in bioanalytical applications for the selective detection of cells and microorganisms such as bacteria. One of the synthesis routes is the so-called stamping method in which template bacteria are pressed mechanically into a thin, gel-like polyurethane layer, which is then cured in the presence of the templates to create cell-specific binding pockets on the polymer. The present work focusses on two specific steps of the imprinting protocol: first, we evaluate the sedimentation of two different groups of bacteria, Escherichia coli and Escherichia blattae, on silicone stamps with respect to the resulting surface coverage, which is a key factor for the efficiency of the imprinting process. Second, we analyse the temperature dependence of the thermal- and dielectric properties of polyurethane during curing by dielectric- and pyroelectric spectroscopy. This provides information for improved curing protocols and on the stability of SIP materials at elevated temperatures.